Characteristics of Vegan Corned Beef (Study of Soybean Paste Proportions : Gluten Flour and Lecithin Addition) - Ruth Marlinauli Manurung; Rosida Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
This study aims to determine the proportion of soybean paste and gluten flour with the addition of soy lecithin on the characteristics of vegan corned beef. This research used a Completely Randomized Design (CRD) with a factorial pattern and three replications. Factor I is the proportion of soybean paste : gluten flour (65:35, 60:40, 55:45). Factor II is the addition of lecithin (0.25%, 0.50%, 0.75%). The data obtained were analyzed using ANOVA and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The results of the research show that there is a real interaction with the values ​​of water content, hardness, emulsion stability, protein content and organoleptic tests. Vegan corned beef with soybean paste treatment: Gluten flour (55:45) with the addition of 0.75% lecithin is the best treatment which produces vegan corned beef with characteristics of 59.72% water content, 31.17% protein content, 17.85 N hardness, emulsion stability 1.90%, as well as a taste preference score of 3.28 (neutral), color 3.44 (neutral), and texture 4.04 (like).